Resisting domestic patriarchy through the latte dad phenomenon: Father involvement and daughters' career orientations in Pandalungan society, East Java - Andiny Mesopiana; Wilodati; Abdullah Mirna Nur Alia (Jurnal Anifa: Studi Gender dan Anak, 2026)
Patriarchal culture continues to shape gender roles and daughters' career orientations in many Indonesian families, including Pandalungan society. Although father involvement has received increasing scholarly attention, limited studies have examined it as a form of resistance to patriarchal culture within the unique socio-cultural context of Pandalungan families. This study examines how the adaptation of the Latte dad phenomenon reflects changing father involvement and its influence on daughters' career orientations. A qualitative case study was conducted involving Pandalungan families in Jember City. Data were collected through in-depth interviews, observations, and documentation and analysed thematically. The findings reveal that resistance to patriarchal culture is manifested through fathers' active participation in childcare, shared domestic responsibilities, support for daughters' education and career aspirations, and egalitarian family decision-making. While parenting practices reflect the influence of both Javanese and Madurese cultural traditions, they increasingly promote independence, autonomy, and equal opportunities for daughters. This study contributes to gender and family studies by conceptualizing the adaptation of the Latte dad phenomenon as an emerging model of father involvement that challenges patriarchal norms and supports daughters' career development in Pandalungan society